Factors relating to hospitalisation and economic burden of paediatric constipation in the state of Victoria, Australia, 2002–2009. (27th June 2014) - Ansari, Humaira; Ansari, Zahid; Lim, Tracy; Hutson, John M; Southwell, Bridget R
<x xml:space="preserve">Abstract</x> Aim Constipation is common, with severe symptoms requiring hospitalisation. Constipation can be a primary (present at admission and requires treatment or investigation) or principal (first listed) diagnosis for hospitalisation. In the USA, constipation is the second most common ambulatory care digestive diagnosis with total costs >US$1.7 billion/year. Incidence of hospitalisation for constipation in children peaks at toilet‐training age. This study determined the burden of paediatric constipation to hospital care in Victoria, Australia. Method The Victorian Admitted Episodes Dataset was analysed retrospectively, examining hospital admissions with a primary diagnosis of constipation in the 7‐year period 2002/2003 to 2008/2009. Results For children, constipation was recorded as a primary diagnosis in 8688 admissions (3.6/1000 of population). In‐hospital prevalence was ∼1.0%. Mean length of stay was 4.4 days (median 1.0, range 0–993, standard deviation 16.7). There were 1121 readmissions in 668 children. Average treatment cost was A$4235/admission (median A$1461, range A$0–$278 816), with annual costs of ∼A$5 505 500. Children in the highest socio‐economic area had ∼50% fewer admissions (P < 0.0001). Predictors of readmission included age 10–18, male gender, rural residence, severe socio‐economic disadvantage, public hospital, planned admission, longer length of stay and association with other medical conditions. Conclusions This study identified that constipation in children is a significant cost burden in Victoria (costing public hospitals ∼A$5.5 million/year). Hospitalisation in Victoria is 10‐fold higher than in the USA with 10% readmissions within a month. We conclude that strategies aimed at reducing hospitalisation for constipation could result in significant savings for the paediatric public health system in Victoria, Australia.